Design and Implementation a Vascular Vein Detector - Abbas Jabbar Lafta Hasuwn; Safa Ameer Hakim Ltyf (American Journal of Botany and Bioengineering, 2025)
The design and implementation of a vascular vein finder serves as a medical monitoring device. It primarily comprises a main board and an LED light source. This device utilizes the varying absorption rates of near-infrared light. The vein finder operates at different wavelengths to facilitate the absorption of light by oxyhemoglobin within the surrounding tissues and vessels. Following photoelectroconversion, the data is filtered to reveal the veins. It is designed to simplify the process of locating veins. It is important to note that it aids in the search for superficial blood vessels beneath the skin, such as in adjunct intravenous diagnostics and the administration of intravenous therapies. This device demonstrates the convenience of blood drawing for individuals of all genders and ages, including children, adults, and the elderly, for whom the blood drawing process can be particularly challenging due to health conditions or the difficulty in visualizing veins clearly. This can lead to delays in the stabilization process and blood withdrawal, causing discomfort to the patient due to repeated attempts at pricking in incorrect locations. The device is capable of detecting superficial veins beneath the skin through the application of infrared light technology research and development. It provides a visual representation at the skin’s surface to assist medical personnel in assessing the direction and distribution of blood vessels. Furthermore, the advanced model features various colors, which significantly enhance clarity and recognition.